Consequences of non-appearance before the international court of justice: Debate and developments in relation to the case nicaragua Vs. Colombia (2018)
The article analyzes the non-appearance before the International Court of Justice motivated by the turbulent reception by the Colombian Government of the 2012 and 2016 sentences of the I.C.J in the cases between Nicaragua and Colombia, with the objective of establishing the consequences of such conduct. Methodologically, the jurisprudence that has applied Article 53 of the Statute, and the different consequences of nonappearance in cases before the Court are studied. Through an analysis of jurisprudence the document discusses the nature of non-appearance, its effects on the sentence, the agents, the applicable law, the evidence and the procedure, to conclude that, although non-appearance is a behavior allowed to the State Parties, it is in general detrimental to its procedural interests, its defense of the case and the administration of international justice as a system, especially in such technical cases as those related to maritime delimitation and liability in relation to alleged violations of sovereign rights and maritime spaces. © 2017 Universidad de Caldas.